Pemanfaatan Limbah Organik Dapur dan Dedak Sebagai Media Pertumbuhan Maggot Black Soldier Fly (BSF) Untuk Efisiensi Pengelolaan Limbah - Agung Fauzi Zunaidi; primadiyanti Yunanto; Ardaniah Ardaniah (Universitas Wiralodra, 2026)
This study aims to explore the effect of kitchen organic waste and bran on the productivity and quality of Black Soldier Fly (BSF) maggots (Hermetia illucens). Kitchen organic waste generated from households has significant potential to be utilized as an alternative feed in maggot cultivation. The research was conducted at the Faculty of Agriculture and Digital Business at Universitas Muhammadiyah Kalimantan Timur from August to October 2024. The method used was a Completely Randomized Design (CRD) with seven different media. The findings revealed that the integration of kitchen organic waste and bran significantly improved both the fresh weight and length of BSF maggots. Notably, the treatment comprising 60% kitchen organic waste and 40% rice bran produced the most optimal results regarding maggot growth. This study underscores the significance of innovative approaches to organic waste management within sustainable agricultural practices. By leveraging the abundant kitchen organic waste, the research not only aids in waste reduction but also provides an effective and eco-friendly feed alternative. Additionally, the results indicate that employing kitchen organic waste and bran as growth substrates for BSF maggots can enhance production efficiency, which can be utilized as a nutrient-dense and sustainable feed source for livestock. This research is anticipated to make a meaningful contribution to the field of organic waste management and the advancement of sustainable feed technologies. Ultimately, the study paves the way for the development of more environmentally friendly agricultural systems, aligning with global initiatives aimed at reducing the ecological footprint of organic waste.